Halogenated quinolines discovered through reductive amination with potent eradication activities against MRSA, MRSE and VRE biofilms1. Issue 41 (7th November 2015) - Basak, Akash; Abouelhassan, Yasmeen; Huigens III, Robert W.
<x xml:space="preserve">Abstract</x> We report the discovery of potent biofilm-eradicating agents identified through a reductive amination reaction on the halogenated quinoline (HQ) scaffold.